Radio frequency cavities for the future circular colliderhadron-hadron (FCC-hh) - Lee, Kin Lim (2017)
Superconducting elliptical Radio Frequency (RF) cavities are proposed to accelerate proton beams in Future Circular Collider (FCC-hh). In this thesis, we focus on using Poisson Super fish for 2D simulation to optimize the geometrical parameters - dome and iris ratios of single-cell superconducting elliptical RF cavities to generate specifi ed optimum figures of merit - resonant frequency, peak electric and magnetic fields on the cavity surface, and quality factor. Comparative studies between Poisson Super fish (2D simulation) and CST Microwave Studio (3D simulation) have veri fied our optimization results in which the optimum dome and iris ratios are 0.74 and 0.51 respectively. Our analysis demonstrates the capabilites of Poisson Super fish in tuning and optimizing geometrical parameters for elliptical RF cavities by achieving optimum fi gures of merit.